Molecular regulation of phenology in trees — because the seasons they are a-changin'. (February 2016) - Ding, Jihua; Nilsson, Ove
Highlights: Trees have to adapt their growth to seasonally changing environmental conditions. This includes the regulation of growth cessation, bud set, dormancy and bud break. The molecular framework for this regulation has just started to be deciphered. The genes involved are conserved with those controlling flowering time in annuals. Abstract : The perennial trees, in contrast to the much more studied annual plants, have to adapt their vegetative growth and development to the sometimes extremely contrasting environmental conditions that occur over the different seasons. Recently, studies of the molecular framework underlying this adaptation in Populus trees is reinforcing the notion that the genetic pathways controlling growth and dormancy cycles have a remarkable conservation with the pathways controlling the regulation of flowering time in annual plants. Insight into these mechanisms will be important for our understanding of how trees will respond to various future global climate scenarios.